A REVIEW OF MOTOR VEHICLE SPEED REDUCTION BEFORE CROSSING SPEED BUMPS ON THE ROADS WITHIN THE MAIN CAMPUS OF UNIVERSITAS NEGERI PADANG - Prananda, Yoga Alex; Oktaviani, Oktaviani (Jurnal Applied Science in Civil Engineering, 2023)
A speed bump is a traffic calming device that is a raised portion of the road surface. Speed bumps are effective in reducing vehicle speed. The purpose of this research is to determine the reduction in vehicle speed at certain distances before crossing speed bumps on the roads within the main campus of Universitas Negeri Padang (UNP). This study was conducted at several points on the roads within the main campus of Universitas Negeri Padang where speed bumps are installed. The survey was carried out in July 2023, spanning 3 days, namely on Monday, Wednesday, and Saturday. The research conducted is quantitative research with a quantitative descriptive method. The data used in this study includes both primary and secondary data. The primary data consists of the speed of vehicles (cars and motorcycles) at distances of 4 meters, 8 meters, and 12 meters before the speed bumps, while the secondary data includes the map data showing the placement of the speed bumps on the roads within the main campus of Universitas Negeri Padang. The research results indicate that the average speed of vehicles passing over the speed bumps on the roads within the main campus of Universitas Negeri Padang experiences a decrease in speed.